Online Disinhibition Effect Among Early Adult Social Media Users - Rayhan Abi Mulya; Desi Susianti (Jurnal Kesehatan dan Kedokteran, 2026)
Social media has become a major space for sharing content and opinions. In online settings, individuals may show behaviors they would usually inhibit in face-to-face interactions, known as the online disinhibition effect. Understanding this tendency among early adults is important because this group is highly active on social media and may be exposed to both constructive and harmful digital interactions. Objective: This study aims to describe the characteristics and level of the online disinhibition effect among early adult social media users. Methods: A quantitative descriptive design was used with 111 early adults (20–40 years; males and females) recruited through non-probability incidental sampling. Data were collected via an online questionnaire (Google Forms) using an adapted Online Disinhibition Scale based on Suler’s dimensions, complemented by demographic items (gender, age, daily duration of use) and two open-ended questions. The instrument was evaluated for validity, item discrimination, and reliability. Data were analyzed using descriptive statistics and frequency-based categorization for open-ended responses. Results: The online disinhibition effect was categorized as high (empirical mean = 85.50; hypothetical mean = 73.50). Male participants showed higher disinhibition than female participants. Higher disinhibition was also observed among participants who used social media longer each day, especially those reporting more than six hours of use. Open-ended responses indicated that anonymity and the absence of face-to-face interaction were common reasons for feeling freer online, and hostile commenting was frequently reported as an activity more comfortably performed on social media than in real life. Implications: Findings support the need for digital well-being efforts targeting early adults, including self-regulation strategies (e.g., screen-time limits, reflection-before-post routines) and digital civility education, alongside platform-level measures that strengthen accountability cues. Originality: This study provides a descriptive baseline of online disinhibition among Indonesian early adults using a psychometrically screened measure and triangulates findings with open-ended evidence linked to key theoretical dimensions.